154 Has the Introduction of the Pryor Risk Score Affected Our use of Coronary Angiography?. (6th June 2015) - Jackson, Matthew; Ciaputa, John; Lee, Alison
Abstract : Background: NICE guideline CG95 for investigating chest pain of new onset (http://www.nice.org.uk/guidance/cg95 ) recommends calculating the Pryor risk score to determine the risk of significant coronary artery disease (CAD). Significant CAD is defined as a lesion >70% in a major epicardial artery or >50% in the left main stem (box 1 of the guideline). Patients with a calculated risk score of 61–90% should be investigated using invasive coronary angiography. Aim: This study evaluates how use of the Pryor risk score has altered the pickup rate of significant CAD on invasive coronary angiography. Design: Retrospective analysis of clinical data and angiography reports covering a 12 month period before and after the introduction of the Pryor score (Sept 2009–Sept 2010 and Jan 2013–Dec 2013 respectively). Method: Patients were identified using the chest pain clinic database and data collected from medical notes. Pryor risk scores were calculated by the nurse specialist in clinic using the standardised Pryor risk score calculator circulated by the Cardiovascular Network. Significant CAD detailed on the angiography report was recorded. Statistical analysis was performed using a two-tailed Z-test for population proportions. Exclusions: Patients who underwent invasive angiography for a reason other than a Pryor score of 61–90% were excluded as were patients with symptoms secondary to known CAD. Results: In the pre-Pryor score group, 34 patients underwent angiography with 27 undergoing Bruce protocol treadmill testing prior to listing. In the Pryor score group, 31 patients underwent angiography. Both groups had similar demographics including gender, age and cardiovascular risk factors. Angiograms were graded into normal, minor disease or significant disease in one, two or three vessels. The results are seen in Table 1 . Only seven (20.6%) patients in the pre-Pryor score group had no significant disease compared to fourteen (45.2%) patients in the Pryor score group (p = 0.034). For patients with a risk score greater than 91%, local Trust policy is to perform a diagnostic angiogram for risk stratification (NICE guidance would suggest medical treatment without further investigation). Including these patients (Table 2 ), 73 angiograms were performed in 2013 with 29 (39.7%) having no significant CAD. Compared to the pre-Pryor score cohort, this still approaches statistical significance with a p value of 0.05. Conclusion: This study suggests that the Pryor risk score puts significantly more patients through invasive angiography who do not have significant coronary disease. Whilst coronary angiography remains 'gold standard', it is not without risk and we question whether using exercise testing to subdivide the patients into 'high' and 'low' risk groups based on exercise capacity could lead to first-line invasive or non-invasive testing respectively to maximise the incidence of significant CAD found at angiography.